Bilosorochka S.I. Olena Pchilka and Nataliia Kobrynska as initiators of ukrainian feminist socio-political movements for gender equality - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The article reveals personal, socio-political qualities and civil positions regarding parity relations of men and women of Olena Pchilka and Natalia Kobrynska who became the founders and leaders of social and political movements for gender equality in Ukraine. The main areas of their activity as to enforcement of women’s rights to emancipation and self-realization in the then society are highlighted.